2016
DOI: 10.11648/j.ejpm.20160405.12
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Impairment in a Semi-urban Community in North-Western Nigeria

Abstract: Abstract:Population based studies to measure the burden of hearing impairment are scarce in sub-Saharan Africa due largely to lack of allocation of resources. This study aims to report the prevalence and possible causes of hearing impairment in a semi-urban community. A cross-sectional community based survey using the World Health Organization Ear and Hearing disorders survey protocol was conducted in 2013. Adults and children hearing assessment was conducted via Pure-tone audiometry for air conduction thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…While Ahmed et al reported male 41.8% and female was 58.2%. 3,4 In our study a prevalence rate of as much as 11% was found in otherwise apparently normal school children. These results are similar to those of Mishra et al and Sapra et al who found a prevalence rate of 21% and 16.60% respectively.…”
Section: Discussionsupporting
confidence: 47%
“…While Ahmed et al reported male 41.8% and female was 58.2%. 3,4 In our study a prevalence rate of as much as 11% was found in otherwise apparently normal school children. These results are similar to those of Mishra et al and Sapra et al who found a prevalence rate of 21% and 16.60% respectively.…”
Section: Discussionsupporting
confidence: 47%